Regulation of (p)ppGpp and Its Homologs on Environmental Adaptation, Survival, and Pathogenicity of Streptococci - Zhang, Tengfei; Zhu, Jiawen; Xu, Jiajia; Shao, Huabin; Zhou, Rui (Frontiers in Microbiology, 2020)
Most streptococci are commensals, pathogens or opportunistic pathogens for humans and animals. Therefore, it is important for streptococci to adapt to the various challenging environments of the host during the processes of infection or colonization, as well as to in vitro conditions for transmission. Stringent response (SR) is a special class of adaptive response induced by the signal molecules (p)ppGpp, which regulate several physiological aspects, such as long-term persistence, virulence, biofilm formation and quorum sensing in bacteria. To understand the roles of SR in streptococci, the current mini-review gives a general overview on: (1) (p)ppGpp synthetases in the genus of Streptococcus, (2) the effects of (p)ppGpp on the physiological phenotypes, persistence and pathogenicity of streptococci, (3) the transcriptional regulation induced by (p)ppGpp in streptococci, and (4) the link between (p)ppGpp and another nutrient regulatory protein CodY in streptococci.